2010
DOI: 10.1111/j.1743-6109.2009.01633.x
|View full text |Cite
|
Sign up to set email alerts
|

Original Research—Surgery: Sexual Function after Loop Electrosurgical Excision Procedure for Cervical Dysplasia

Abstract: Introduction Loop electrosurgical excision procedure (LEEP) is an effective tool for management of cervical dysplasia. However, removal of a part of the cervix might have a negative impact on sexual function. Aim To examine the effect of LEEP on overall sexual satisfaction and other specific aspects of sexual function in women with cervical dysplasia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 12 publications
2
19
0
2
Order By: Relevance
“…Gravina et al 13 found that the urethrovaginal tissue was thinner overall in women who were unable to experience vaginally elicited orgasm. We have complementary analogous data that loop electrosurgical excision procedures of the cervix adversely affect orgasm in 11% of patients 44 . In consequence, any surgical intervention in the female genitalia, especially the vagina, cervix, or anterior vaginal wall, can adversely influence neural input to orgasm.…”
Section: Discussionsupporting
confidence: 55%
“…Gravina et al 13 found that the urethrovaginal tissue was thinner overall in women who were unable to experience vaginally elicited orgasm. We have complementary analogous data that loop electrosurgical excision procedures of the cervix adversely affect orgasm in 11% of patients 44 . In consequence, any surgical intervention in the female genitalia, especially the vagina, cervix, or anterior vaginal wall, can adversely influence neural input to orgasm.…”
Section: Discussionsupporting
confidence: 55%
“…Servikal intraepitelyal neoplazi nedeni ile tedavi edilen hastalarda tedavi sonrasında özellikle cinsel istek ve ilgide, cinsel ilişki sıklığında anlamlı azalmalar bil-dirilmiştir (13,14) . Bunun nedeni olarak da özellikle tanı ve tedavinin neden olduğu anksiyeteye bağlı psikoloijk etkilerin olduğu vurgulanmıştır (24) .…”
Section: Discussionunclassified
“…Cinsel istek bozukluğu, uyarılma ve orgazm bozuklukları, ağrılı cinsel ilişki şeklinde görülebilmektedir (12) . Literatürde LEEP'in kadın cinsel fonksiyonları üzerine etkisini araştıran çalışmalar yapılmıştır (4,13,14) . (15) .…”
Section: Introductionunclassified
“…15,18,20 These studies postulated that the domains significantly affected were psychological in nature, possibly attributed to the anxiety associated with the diagnosis and treatment of CIN. It is not unreasonable to hypothesize that similar psychological components of sexual health are negatively affected in women treated for VIN.…”
Section: Discussionmentioning
confidence: 99%
“…19 This study found that desire was significantly decreased after treatment, while the other domains were unaffected. Inna et al 20 used a self- designed questionnaire and found that frequency of sexual intercourse, dysmenorrhea, and dyspareunia after LEEP were not significantly different following treatment. However, overall sexual satisfaction, orgasmic satisfaction and vaginal elasticity were significantly decreased up to one year following LEEP.…”
Section: Effects Of Treatment For Cervical Dysplasia On Sexual Healthmentioning
confidence: 99%